EDUCATIONAL INTERVENTIONS FOR BULLYING: INTEGRATING PETIK LAUT TRADITION TO FOSTER POSITIVE STUDENT BEHAVIOR - Supriyatin; Isriyah, Mudafiatun; Rahmawati, Weni Kurnia (EDUCATIONE, 2025)
Verbal bullying is a pervasive issue in educational settings, characterized by insults, harsh language, and derogatory comments that can have severe psychological and emotional impacts on students. This study aimed to develop a culturally relevant intervention model that integrates the values of the Petik Laut tradition with cognitive-behavioral therapy (CBT) to reduce verbal bullying at MTS Al Haromain, Mojosari, Puger. The research utilized a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which included the identification of bullying prevalence, module development, expert validation, and pilot testing with 53 students (Sa et al., 2020). The findings revealed that the Petik Laut tradition, emphasizing mutual respect, community solidarity, and environmental stewardship, significantly reduced verbal bullying and enhanced students' social resilience, fostering positive behavioral changes. This study contributes to the field of educational psychology by demonstrating the effectiveness of integrating local cultural values into structured educational interventions, offering a novel approach to bullying prevention that aligns with both cultural sustainability and contemporary educational goals. The results underscore the importance of culturally responsive education and highlight the potential for broader application in diverse educational contexts. Future research should explore the long-term impacts of this approach on student outcomes, including academic achievement, social well-being, and community engagement.